2021
DOI: 10.1002/cbin.11650
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of P53 promotes nucleus pulposus cell apoptosis in intervertebral disc degeneration through upregulating NDRG2

Abstract: P53 is an apoptosis marker which is involved in determining nucleus pulposus (NP) cell fate. Little is known about P53 interaction with N‐Myc downstream‐regulated gene 2 (NDRG2) in intervertebral disc degeneration (IVDD). Here, we studied the role of the P53‐NDRG2 axis in IVDD. We found that NDRG2 was expressed in NP tissue obtained from patients with IVDD. The level of NDRG2 was positively related to the severity of IVDD, as determined by Pfirrmann grading. Subsequently, we overexpressed NDRG2 in human NP cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…HIF-1 promotes but P53 hinders these genes' expression (37,38). Moreover, HIF-1 and P53 show negative and positive regulatory effects on NDRG2, respectively (39)(40)(41)(42). Hence, we believe that the regulation of NDRG2 on glycolysis ux is accomplished by cooperating with C-Myc, HIF-1, and P53 to regulate the expression of glycolytic genes.…”
Section: Discussionmentioning
confidence: 91%
“…HIF-1 promotes but P53 hinders these genes' expression (37,38). Moreover, HIF-1 and P53 show negative and positive regulatory effects on NDRG2, respectively (39)(40)(41)(42). Hence, we believe that the regulation of NDRG2 on glycolysis ux is accomplished by cooperating with C-Myc, HIF-1, and P53 to regulate the expression of glycolytic genes.…”
Section: Discussionmentioning
confidence: 91%
“… 39 Moreover, as an apoptosis marker, elevated P53 stimulates apoptosis of nucleus pulposus cells and accelerates IVDD progression. 40 Previous clinical research revealed that the level of IL-1β in the IVD of IVDD patients was significantly elevated. 41 Mechanism study demonstrated that IL-1β accelerated the production of Caspase-3, P53 and Bax in IVD but reduced the production of anti-apoptotic proteins Bcl-2 as well as matrix proteins Col2 and aggrecan.…”
Section: Discussionmentioning
confidence: 99%
“…As reported (14), we induced the NPCs to become DNPCs to carry out the following molecular mechanism study. Moreover, because of technical and periodic reasons, we cannot establish a rat model of IDD as the previous study (28) to explore the molecular regulatory mechanism of DNPCs. At present, we only verified the results in existing cell lines.…”
Section: Discussionmentioning
confidence: 99%